PERAN PEREMPUAN DALAM PEMBANGUNAN BERKELANJUTAN WOMEN IN SUSTAINABLE DEVELPMENT - Yusriani Sapta Dewi (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2011)
The United Nations are formally commited to gender mainstreaming within all policy areas and programs. In 1992 the United Nation Conference on Environment and Development produced Agenda 21, which recognized women as one of the nine major groups whose active participation is essential to sustainable development. It was agreed that the advancement of women is indeed a pre requisite for making sustainable development a reality. The World Conference on Women in 1995 adopted the Beijing Platform for Action, in which governments agreed to implement gender mainstreaming. Other United Nation conference have also acknowledged the importance of adopting a gender specific approach to implementing policies; gender equality has been identified as one of Millennium Development Goals and designated as a crosscutting theme for work of the commission on sustainable organizations, national government, and most civil society groups still fail to integrate gender perspectives adequately into their policies and their actions.